Lingering effects of relative age in basketball players' post athletic career - Schorer, J.; Neumann, J.; Cobley, S.; Tietjens, M.; Baker, J. (International Journal of Sports Science and Coaching, 2011)
Relative age effects (RAEs) refer to participation and attainment variations among individuals within age-based cohorts, typical in youth-sport systems. While RAEs have often been demonstrated in active athletes, this exploratory study examined whether RAEs were influential on post athletic careers such as referees, coaches and commissioners. Data on 142 players, 26 coaches, 32 referees, and 16 commissioners were obtained from the First German basketball league for the 2009/10 season. Chi-square revealed significant RAEs for players, x2(3) = 12.99, p < .01, w = .30, and for the combined group of post-athletic careers, x2(3) = 10.22, p = .02, w = .37, suggesting a lingering long-term trend from youth basketball to post athletic careers. RAEs are a persistent inequality in high performance sport, potentially affecting post-athletic careers. An important limitation to the current data is noteworthy. Without longitudinal data it is not possible to determine conclusively whether this effect is a result of athletespecific advantages, `lingering` into the post-athletic career or some secondary factor related to relative age that manifests later in one`s development. Although it is highly likely that the relative age effect is the result of biases that occur early in development (when differences between relatively older and younger are greatest), this remains an important avenue for future research.